K-State First CAT Community Program Learning Assistant Guide 2012-2013 - Kansas State University, K-State First (Kansas State University. K-State First., 2012)
A guide for Learning Assistants (LAs) in Connecting Across Topics (CAT) Communities. Provides an overview of all K-State First programs, as well as specific guidelines and suggestions for in-class activities, co-curricular events, and how best to work with instructors and other LAs in the teaching/learning process. Also covers important guidelines for Residential Learning Assistants and their roles in Housing.
Keywords: Guide; CAT communities; First-year experience program; Learning Assistants; Living-learning communities; Brochures